2010
DOI: 10.1139/f10-070
|View full text |Cite
|
Sign up to set email alerts
|

Selenium incorporation in fish otoliths: effects of selenium and mercury from the water

Abstract: To study fish migration using otolith microchemistry, it is important to understand the relationship between elements in the otoliths and in the surrounding water, including potential interactions with other elements. Selenium (Se) is a trace element with strong affinity for mercury (Hg). To test if Se is a reliable tracer for fish migration, the effects of dissolved Se and Hg concentrations on Se incorporation in fish otoliths were investigated experimentally. Brown bullheads ( Ameiurus nebulosus ) were reare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Because Onondaga Lake contains high levels of mercury and because Se was found at relatively high concentrations in fish otoliths, we at first hypothesized that elevated mercury in fish would somehow facilitate the incorporation of Se into otoliths. However, an experiment that treated fish with various combinations of Se and Hg showed that increased Hg resulted in decreased incorporation of Se into otoliths (Lochet et al 2009). Thus, despite moderately elevated Se concentrations in Onondaga Lake compared to other areas within the region, we cannot explain why Se appears to be elevated in otoliths of Onondaga Lake fish compared to Oneida Lake fish.…”
Section: Discussionmentioning
confidence: 99%
“…Because Onondaga Lake contains high levels of mercury and because Se was found at relatively high concentrations in fish otoliths, we at first hypothesized that elevated mercury in fish would somehow facilitate the incorporation of Se into otoliths. However, an experiment that treated fish with various combinations of Se and Hg showed that increased Hg resulted in decreased incorporation of Se into otoliths (Lochet et al 2009). Thus, despite moderately elevated Se concentrations in Onondaga Lake compared to other areas within the region, we cannot explain why Se appears to be elevated in otoliths of Onondaga Lake fish compared to Oneida Lake fish.…”
Section: Discussionmentioning
confidence: 99%
“…SR-μXRF scanning on a macro scale is a recent and actively developing technique in the study of both modern and ancient materials (Lintern et al, 2009;Bertrand et al, 2012;Anné et al, 2014). Application of milli-to microbeam synchrotron XRF mapping to otoliths is in its early stages, with some environmental and ecological studies on modern samples (Nakai et al, 1999;Limburg et al, 2007Limburg et al, , 2010aLimburg et al, ,b, 2015Lochet et al, 2010;Nakazawa et al, 2012), and one on modern and archaeological otoliths using increased Mn content as an indicator of hypoxia (Limburg et al, 2011). The high incident flux and sensitive detectors found in state-of-the-art SR-μXRF setups permit collection of maps of whole otoliths or significant portions in reasonable time periods.…”
Section: Lateral Resolution and Data Alignment In Sclerochronologicalmentioning
confidence: 99%
“…The absolute quantification of other elements may also be inaccurate as a result of poor SNR, due to their low concentrations and the short count time accepted as a compromise for faster mapping of Sr. Using longer count times and/or higher incident photon flux, quantitative maps of trace elements in otoliths by SR-μXRF, including Br, Ba, and Se have been reported in the literature (Limburg et al, 2007(Limburg et al, , 2010a(Limburg et al, ,b, 2011Lochet et al, 2010). SR-μXRF point analyses with count times of 1000 s have successfully quantified Sr and Ba, and detected Y, Zr, and Nb in cuttlefish statoliths (Zumholz et al, 2007).…”
Section: Quantification Processmentioning
confidence: 99%
“…Selenium (Se) is another element that could serve as a useful marker for diadromous migrations. Importantly, Se is taken up in otoliths in proportion to environmental abundance (Palace et al , 2007; Lochet et al , 2010). Within the periodic table, it is classified as Group 16, a chalcogen or oxygen‐group member.…”
Section: Constituentsmentioning
confidence: 99%
“…Within organic tissues, Se competes with mercury for methyl binding sites (Yang et al , 2008). In an experiment using the relatively rare stable isotope 78 Se together with dissolved Hg, Lochet et al (2010) found that the presence of Hg can significantly lower otolith Se concentrations. Thus, complex interactions such as this may alter Se incorporation into otoliths.…”
Section: Constituentsmentioning
confidence: 99%